The FCTC dilemma on heated tobacco products - Lukasz Gruszczynski; Margherita Melillo (BMC, 2020)
Abstract Background In October 2018, the Conference of the Parties of the Framework Convention on Tobacco Control (FCTC or Convention) adopted its first decision on novel and emerging tobacco products, including heated tobacco products (HTPs). The decision remains ambiguous, e.g. by making a distinction between tobacco sticks and HTP devices. Against this background, the article seeks to answer two interrelated questions: whether and to what extent HTPs are covered by the FCTC, and whether regime provided by the Convention is suitable for their regulation. Results HTPs need to be classified under the FCTC as tobacco products. The distinction made by the Conference of the Parties between sticks and devices leads however to unsatisfactory results as it creates loopholes in tobacco control standards existing at the international level. A better approach, as argued in this article, is to conceptualize the notion of 'tobacco products' in functional terms as a combination of both a device and stick. While subjecting HTPs to all FCTC disciplines is, in light of our current scientific knowledge, a rational approach, such classification can be modified in the future once a sufficient amount of new evidence on their risk profile is collected. Any decision on the optimal regulatory model for HTPs will need to take into account not only health risks and potential benefits for individual users, but also the specific systemic concerns (e.g. HTPs as a gateway product). The state of scientific research is however not the only factor that will determine the fate of HTPs under the Convention. What is equally important is a conceptualization of the FCTC's objectives. If a complete eradication of the tobacco epidemic is the ultimate goal, reduced levels of risk may not be enough to justify the different (i.e. more lenient) regulatory regime for HTPs. Conclusions The Conference of the Parties should clarify the definition of tobacco products in light of recent changes in the market. When designing the regulatory regime for HTPs under the FCTC in the future, one has to consider not only scientific evidence but also pay attention to the objective of the Convention (or more generally to the values that underlie the current tobacco control paradigm).